Orally Active Antiviral Tripeptide Glycyl-Prolyl-Glycinamide Is Activated by CD26 (Dipeptidyl Peptidase IV) before Transport across the Intestinal Epithelium - Hubatsch, Ina (American Society for Microbiology, 2005)
The tripeptide amide glycyl-prolyl-glycinamide (GPG-amide) is a new antiretroviral drug candidate, but its absorption mechanism is unknown. In this investigation, the transport and metabolism of GPG-amide were studied in a model of the human intestinal epithelium, Caco-2 cell monolayers. The results show that when the tripeptide amide came into contact with the apical enterocyte membrane, it was degraded by CD26 (dipeptidyl peptidase IV) to glycylproline and the antiretrovirally active metabolite glycinamide. Glycinamide retained antiretroviral activity in vitro after transport through the Caco-2 cell monolayers. The transport of glycinamide across Caco-2 cell monolayers occurred via passive diffusion with an apparent permeability coefficient of about 2 × 10(−6) cm s(−1), which suggests that it is absorbed by the oral route in sufficient amounts to be considered for oral administration. In conclusion, the tripeptide GPG-amide acts as a prodrug that is activated by CD26 to release the orally active antiretroviral compound glycinamide.